Lesson Study: Penerapan STAD Kontekstual untuk Meningkatkan Hasil Belajar dan keterampilan Proses Sains - Najah Sholehah (Journal of Classroom Action Research, 2022)
Based on the results of observations showed that animal diversity learning in Semester 3 students are less involved in learning activities, so the process skills and learning outcomes of students need to be improved. Efforts to improve student process skills and learning outcomes by applying the STAD learning model combined with contextual approaches. This study uses a type of Lesson Study-based class action research that is carried out in 2 cycles. The results showed that the application of the STAD learning model combined with contextual approaches: (1) improved student process skills based on observation results by 97.51; (2) Classically improve student learning outcomes from cycle one 1 to cycle 2 by 6.49% with learning completion reaching 100%